(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2024)
Globally, the healthcare sector is the pivot and integral part of human lives. Any error committed in the clinic services might lead to defects or the termination of life. In the rapidly evolving field of healthcare, efficient and accessible appointment scheduling plays a crucial role in ensuring timely and quality care for patients. This article is centered around creating a Patient Appointment Scheduling System, with a focus on handling registration and management, as well as managing bookings or making appointments and scheduling sessions at Aliko Dangote University of Science and Technology, Wudil (ADUSTECH Wudil). Identification of the drawbacks of the existing traditional system leads to the design of a computerized system, which is more user-friendly and GUI-oriented. HTML, PHP, CSS, JavaScript, and MySQL were used for the development. Note that performance was improved to 92% from using the traditional system. Similarly, the productivity of participants increased to 90%. Furthermore, the waiting time for patients to be attended was enhanced to 90% in the proposed system.